Impact of quantitative dietary guidance on postoperative outcomes in patients undergoing transjugular intrahepatic portosystemic shunt surgery: a retrospective cohort study - Xu, Yue; Yin, Qin; Xiao, Jiangqiang; Zhao, Qing; Chen, Xiaotian; Zhang, Ming; Gao, Bo (Frontiers in Nutrition, 2026)
BackgroundThe optimal nutritional management strategy after transjugular intrahepatic portosystemic shunt (TIPS) procedure in cirrhotic patients remained controversial. A quantitative dietary intervention approach was developed for patients in the post-TIPS period, and its impact on clinical outcomes was evaluated in this study.MethodsThis study was a retrospective, non-randomized controlled cohort study. A total of 92 cirrhotic patients who underwent TIPS were enrolled. Following TIPS, patients were categorized into two groups according to whether they received TIPS-oriented quantitative dietary intervention during hospitalization. The quantitative dietary guidance group received individualized and quantitative dietary instructions after TIPS, and the usual care group served as control. The primary endpoint was death, and the secondary endpoint was overt hepatic encephalopathy (OHE) occurrence. Kaplan–Meier survival analysis and Cox proportional hazards regression models were used to evaluate the association between quantitative dietary intervention and outcomes.ResultsThe quantitative dietary guidance group (n=54) showed significantly lower mortality rates (5.56% vs. 21.05%, p=0.05) and OHE occurrence (12.96% vs. 36.84%, p=0.01) during follow-up than the usual care group (n=38). Liver-related mortality was also significantly lower in the quantitative dietary guidance group (1.85% vs. 15.79%, p=0.04). Multivariate Cox regression analysis demonstrated that the dietary intervention was independently associated with lower liver-related mortality risk (HR 0.09, 95% CI 0.01–0.75, p=0.03) and OHE risk (HR 0.34, 95% CI 0.14–0.85, p=0.02). Survival analysis demonstrated that the OHE probability was significantly lower in the quantitative dietary guidance group compared to the usual care group (HR 0.32, 95% CI 0.13–0.77, p=0.01), as was liver-related survival (HR 0.13, 95% CI 0.02–0.66, p=0.03).ConclusionA structured quantitative dietary intake protocol following the TIPS procedure could improve survival rates and reduce the incidence of HE. These findings highlighted the importance of TIPS-oriented nutritional management for cirrhotic patients.